(untitled) (Global Journal of Medical Research, 2016)
This study evaluates divalent ion abnormalities (DIA) and the hormonal changes throughout the spectrum of early CKD stages (1-4) as defined by K/DOQI. A total of 96 patients (48.96% males, mean age 62±13 yrs) with CKD 1 to 4, were prospectively evaluated and followed-up. There were (20, 27, 32, and 17 patients in CKD-1, 2, 3, and 4 respectively). The diagnosis was confirmed by renal biopsy, Table -1.Mean serum creatinine (62±32 umol/L). Plasma levels of calcium, phosphorus, calcitriol (CTRL), and parathyroid hormone (PTH) were evaluated among the groups. A 24-hour urinary creatinine, calcium (Uca), phosphorus (Up), creatinine clearance and fractional excretion of calcium (FeCa), and phosphorus (FeP) were also compared. PTH was measured using the standard IRMA test (normal values 10-50 pg/dl), and calcitriol was measured by RIA test (normal values are 74.5 -169 pmol/l). The exclusion criteria are nephrolithiasis, hypercalcemia, proteinuria >3g/24 hrs, previous renal transplant, and therapy with steroids or anticonvulsants (Phenytoin).